NETworking for health and in disease: neutrophil extracellular traps in pediatric surgical care - Dölling, Maximilian; Herrmann, Martin; Boettcher, Michael (Children, 2024)
This comprehensive review examines the role of Neutrophil Extracellular Traps (NETs) in pediatric surgery. Focusing on NET formation, functions, and implications, this study highlights their dual impact in infection control and contribution to tissue damage after surgery. It covers the role of NET formation in a range of pediatric conditions including immunothrombosis, formation of peritoneal adhesions, appendicitis, burns, gallstones, tumors, and necrotizing enterocolitis (NEC). The results underscore the significance of NETs in fighting infections and their association with complications like sepsis and delayed wound healing. The breakdown products of NETs as a diagnostic tool of the clinical course of acute appendicitis will also be discussed. Understanding NET formation in the pathophysiology can potentially help to find new therapeutic approaches such as the application of DNase and elastase inhibitors to change the clinical course of various diseases in pediatric surgery such as improvement of wound healing, adhesion formation, NEC, and many more.
Gesehen am 15.08.2024